Use of Electronic Devices in the Teaching and Learning of the English Language in Oyo State Senior Secondary Schools - Aremu, Moses; Odekunbi , Sunday; Adegbola, Ismail (African Journal of Education and Practice, 2024)
Purpose: The dwindling standard of Nigerian students' performances in SSCE English language has become worsened. As a result, this study will focus at employing electronic approach in language teaching called Computer Assisted Language Teaching (CALL) to improve the learners' poor performances in WASSCE, NECO and UTME and other English language external examinations. Computer Assisted Language Learning (CALL) is a novel electronic approach to language pedagogy being introduced in 1980s in Deakin University, USA was used in this research as a theoretical tool. Methodology: This research used Brade's (2007) teleconferencing and Sussaine Herring's (2001) Computer Assisted Language Learning (CALL) as theoretical framework for the study. Coupled with this, questionnaires was administered among 360 students and 36 teachers from 18 purposively selected senior secondary schools in Oyo State. Stratified randomly sampling approach was used in selecting the respondents. Besides, electronic tools like projector and other power-point gadgets down-linked equipment gadgets that are used in electronic language teaching called tele-conferencing was purchased for teaching the respondents. A lecture room was furnished for keeping the gadgets purchased and for using video or tele-conferencing in language teaching in teaching the respondents. Findings: The findings revealed that this electronic approach to English language in Nigeria has improve the poor standard of students' performances in external examinations like WASSCE, NECO and also improve students' communicative and linguistic competence in English language in Oyo State. Unique Contribution to Theory, Practice and Policy: The government and educational authorities in Oyo State should prioritize investments in digital infrastructure, including providing schools with an adequate number of electronic devices and ensuring reliable internet connectivity. This will facilitate seamless integration of technology into the teaching and learning process.